Fotoproduksi Meson-Eta pada Proton - Alhidayatuddiniyah T.W. (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
This research is aimed at calculating the results of eta-meson photoproduction on protons using an isobar model to produce numerical data corresponding to the experimental data by investigating the reaction of photoproduction ,. The amplitude transitions at the center of mass frame are translated into amplitude of Chew-Goldberger-Low-Nambu (CGLN). The amplitude of the terms involving the channel-s, -t, and -u in Born term and Resonans term. The reaction of photoproduction is developed using isobaric models. Formulated also the differential cross section and polarization of photons to see the contribution of each channel. Model parameters are determined by ?tting the experimental data. The result is this model is not good enough to produce numerical data in accordance with the experimental data.So, further study is needed to fit the experimental data and substitute the form factor into the model in order to obtain the parameter values present in the model.